Mga Munting tinig small voices - Portes, Gil M.; College Assurance Plan (Philippines).; Teamwork Productions ([Metro Manila] Warner Home Video (Phils.), 2003)
An idealistic young teacher challenges the cynicism and strictures of life in a poverty-stricken Philippine village by reaching her young students through music.
Disc 1: 56 min. -- disc 2: 52 min.
VCD.
Directed by Gil. M. Portes ; producers, Gil M. Portes, Ray Cuerdo ; screenplay, Gil M. Portes, Adolfo B. Alix, Jr., Senedy H. Que
Alessandra de Rossi, Gina Alajar, Amy Austria, Dexter Doria.
Star Awards Movie of the Year, 2003 ; Famas Awards Best Director and Best Picture, 2003 ; Gawad Urian Best Direction and Best Picture ; Palm Beach International Film Festival Best Feature, 2003.
Keywords: Teachers -- Drama; Teacher-student relationships -- Drama; Feature films